Promoting L2 English Speech Fluency in Finnish General Upper Secondary Education : A Survey of Textbooks and Teachers’ Perceptions - Rihko, Leena (My University, 2024)
The topic of this minor subject thesis is promoting speech fluency. The context of the study is general upper secondary education in Finland, and the aim of the study is to examine how speech fluency is promoted in textbooks and how teachers view the usefulness of textbooks in teaching fluency. The textbook survey included 32 textbooks from four textbook series for upper secondary school English: Insights, On Track, Open Road and ProFiles. Teachers’ perceptions were studied with a questionnaire that was answered by 26 upper secondary school English teachers. There were 64 fluency-focused activities in the data, and out of these, 39 activities focused on formulaic sequences, while 18 activities addressed consciousness-raising or strategy training. Repetition or pre-task planning was addressed in four activities and discourse markers in three activities. The main results of the questionnaire were that all the teachers found it important that textbooks include activities to promote speech fluency, and over 80 % wished to have more fluency-enhancing activities in textbooks. Still, over 60 % were satisfied with the number of fluency activities. The results imply that the importance of speech fluency is recognised in textbooks and by teachers, but teachers are expected to supplement textbooks with other fluency-focused activities. A large variety of fluency activities in textbooks would be beneficial.
Keywords: speech fluency, L2 teaching, upper secondary education, textbooks